2019
DOI: 10.1186/s13002-019-0286-3
|View full text |Cite
|
Sign up to set email alerts
|

Ethnobotanical knowledge among the semi-pastoral Gujjar tribe in the high altitude (Adhwari’s) of Churah subdivision, district Chamba, Western Himalaya

Abstract: BackgroundThe wild plants not only form an integral part of the culture and traditions of the Himalayan tribal communities but also contribute largely to the sustenance of these communities. The tribal people use large varieties of wild fruits, vegetables, fodder, medicinal plants, etc. for meeting their day-to-day requirements. The present study was conducted in Churah subdivision of district Chamba where large populations of Muslim Gujjars inhabit various remote villages. These tribal people are semi-pastora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(32 citation statements)
references
References 85 publications
3
29
0
Order By: Relevance
“…As NTFPs-derived cash income is the principal cash earner among the poorer households, NTFPs do not, however, serve as mere gap fillers or just a safety net; they are a cornerstone in household livelihood strategies as has been found elsewhere [ 40 – 42 ]. The role of NTFPs is particularly important in the Himalayan region where a large proportion of the rural population depends on them as a source of wild fruits, vegetables, fodder, medicinal plants, food, fibre, dye, and other useful materials for daily needs and trade [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As NTFPs-derived cash income is the principal cash earner among the poorer households, NTFPs do not, however, serve as mere gap fillers or just a safety net; they are a cornerstone in household livelihood strategies as has been found elsewhere [ 40 – 42 ]. The role of NTFPs is particularly important in the Himalayan region where a large proportion of the rural population depends on them as a source of wild fruits, vegetables, fodder, medicinal plants, food, fibre, dye, and other useful materials for daily needs and trade [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…Locally available and commercially valuable natural resources have the potential to improve the livelihoods of rural mountain people [ 51 , 52 ]. Such diversity supports to health care and nutrition and can significantly contribute to rural wellbeing through proper planning [ 37 , 53 , 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…Ahmad et al [54] reported the utilization of most of the plant species for medicinal and fodder purposes in Pakistan Himalaya. The highest proportion of plant species were utilized for medicinal purposes followed by fodder in Azad Jammu and Kashmir [55] and Gujjar, Western Himalaya [56]. Due to higher dependence on medicinal plants for treating various ailments and demand by the pharmaceutical industry, the locals especially Amchis, shepherds and herbal drug dealers prefer the medicinal usage of local flora.…”
Section: Discussionmentioning
confidence: 99%
“…The water extract obtained by soaking the root bark in water is used for the treatment of diabetes (Ahmed et al, 2004). The whole plant is used to treat diabetes in Chamba district of Himachal Pradesh, West Himalaya, India (Rana et al, 2019). The Bhotiya tribal community of the Central Himalayan region of India used B. lycium roots with water for the treatment of diabetes (Phondani et al, 2010).…”
Section: Ethnopharmacology Of Berberis Spp Against Diabetes and Othementioning
confidence: 99%
“…A decoction prepared from the roots of Berberis plants is one of the common traditional recipes for the treatment of diabetes (Neag et al, 2018). Various studies have reported the traditional uses Berberis plants for the treatment of metabolic diseases (e.g., diabetes and hyperlipidemia) in many countries, including India, Pakistan, China, and Iran (Hamayun et al, 2006;Uniyal et al, 2006;Rahimi Madiseh et al, 2014;Rana et al, 2019). Various bioactive compounds, such as alkaloids, polyphenols, flavonoids, anthocyanins, etc., have been found in Berberis species along with various vitamins and mineral components (Andola et al, 2010;Srivastava et al, 2015;Belwal et al, 2016;Belwal et al, 2017).…”
Section: Introductionmentioning
confidence: 99%